Frequency and Causes of Dental Complaints in the Yazd Medical Council Organization between 2017 and 2022 - Yasaman Sabaghzadegan; Sina Amini-Bahabadi; Fatemeh Owlia (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Currently, even with the extensive and advanced resources available in dentistry, patient dissatisfaction and complaints have increasingly become more prevalent. To acquire accurate and practical data for enhancing dental services’ quality and reducing the expenses linked to complaints, research must be performed to explore dental grievances. This research sought to identify the rate and reasons behind complaints made against dentists to the healthcare system from 2017 to 2022.  Methods: This cross-sectional research entailed gathering existing data and examining complaint records from dentists at the Yazd Medical Council Organization. The information was gathered through observation and by filling out applicable checklists. Subsequently, thedata underwent analysis through  SPSS version 16, utilizing with a chi-square test and Spearman correlation. The threshold for statistical significance was established at p≤ 0.05. Results: According to the results obtained, the majority of complaints were directed towards general dentists, especially males. Over fifty percent of the individuals who filed complaints were female. The most frequent types of dental issues were associated with surgery, endodontic, and prosthetic care. In 52.9 percent of the cases, dentists were deemed guilty, primarily due to complaints related to malpractice. Conclusion: Dental practitioners must increase their knowledge regarding case selection and dental management to improve their practice.